2016
DOI: 10.14689/ejer.2016.64.13
|View full text |Cite
|
Sign up to set email alerts
|

Problem-Solving Training: Effects on the Problem-Solving Skills and Self-Efficacy of Nursing Students

Abstract: Problem Statement: Problem-Solving (PS) skills have been determined to be an internationally useful strategy for better nursing. That is why PS skills underlie all nursing practice, teamwork, and health care management, and are a main topic in undergraduate nursing education. Thus, there is a need to develop effective methods to teach problem-solving skills. The present study, as a first study in Turkey, may provide valuable insight for nurse academicians employed at üniversities. Purpose of the Study:This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
0
15

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 21 publications
6
39
0
15
Order By: Relevance
“…In our study, evaluative approach and total scale scores of constructivist approach were found to be higher than control group. Similarly to our study, Ançel (2016) found that students who received problem solving education had a statistically significant change in the 'thinking approach', 'evaluative approach' and 'planned approach' subscale scores and that students perceived themselves more competent (Ançel, 2016). Kanbay and Okan (2017) determined that the overall problem solving skills of students who received critical thinking education were higher (Kanbay and Okanlı, 2017).…”
Section: Discussionsupporting
confidence: 82%
“…In our study, evaluative approach and total scale scores of constructivist approach were found to be higher than control group. Similarly to our study, Ançel (2016) found that students who received problem solving education had a statistically significant change in the 'thinking approach', 'evaluative approach' and 'planned approach' subscale scores and that students perceived themselves more competent (Ançel, 2016). Kanbay and Okan (2017) determined that the overall problem solving skills of students who received critical thinking education were higher (Kanbay and Okanlı, 2017).…”
Section: Discussionsupporting
confidence: 82%
“…The dynamic and ongoing involvement of clinical staff can bridge the gap between theory and practice [36]. Table 3 Comparing mean change of social problem solving, critical thinking and decision making skill score before and after of intervention between experimental and control groups Table 4 Comparing mean scores of social problem solving, critical thinking and decision making skill before and after of intervention in experimental and control groups Ancel (2016) emphasizes that structured and managed problem-solving training can increase students' confidence in applying problem-solving skills and help them achieve self-confidence. He reported that nursing students want to be taught in more innovative ways than traditional teaching methods which cognitive skills training should be included in their curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…He reported that nursing students want to be taught in more innovative ways than traditional teaching methods which cognitive skills training should be included in their curriculum. To this end, university faculties and lecturers should believe in the importance of strategies used in teaching and the richness of educational content offered to students [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study carried out with nursing students, it was also observed that there is a relation between academic selfefficacy perception and problem solving proficiency [22]. In a study conducted at the faculty of nursing, a positive, medium-level but statistically insignificant relation between post training problem-solving ability and self-efficacy has been found [23]. In our study, it was observed that the problem solving proficiencies and self-efficacy perceptions of the students that study at the physiotherapy and rehabilitation, nutrition and dietetics and nursing departments of the faculty of health sciences are related at a low level.…”
Section: Discussionmentioning
confidence: 96%